Innovative Behavior as a Mediator of Organizational Climate and Job Stress’ Influences on Performance - Lathifah, Meisy; Wahyuningsih, Rr. Sri Handari (International Journal Labs, 2022)
Performance and job stress are two connected factors that influence one another. A low to moderate degree of job stress will positively affect performance, which will be at its best. When there is less pressure on the staff, they often do their tasks more quickly and more effectively. On the other hand, low work performance will result if employees are under a lot of stress and have a ton of work to do. The objective of the research is to identify the innovative behaviors mediation role’s towards organizational climate, along with job stress towards Muhammadiyah University of Yogyakarta postgraduate student which already employed. Implementing the quantitative approach, data of the research obtained by spreading questioner towards Muhammadiyah University of Yogyakarta postgraduate students who were already employed. Purposive data sampling technique was used, resulting in 89 respondents. SEM-PLS (Purposive sampling) implentation is to analyze suggested relation model. Based on the results of the research, employee’s performance can be improve by the implementation of innovative behavior. Innovative behavior as variable of mediation may applied towards organizational climate and job stress in order to improve employee’s performance.